Overview Laporan Keuangan UPK Mitra Mandiri di Kec. Pragaan, Sumenep, Madura (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
Financial statements are a form of delivery, notification or liability that contains about a company’s financial information to describe the performance of the company. SAK ETAP or financial accounting standards for entities without public accountability are accounting standards used by entities that do not have significant accountability and and publish financial statements for the same purposes. The purpose of this study is to find out the results of financial statement analysis in accordance with SAK ETAP at UPK Mitra Mandiri in Pragaan Sumenep Madura District. The methods used in this study are mixed because they focus on collecting, analyzing, and mixing quantitative and qualitative data in one study or series of studies.